2006
DOI: 10.1897/05-015r.1
|View full text |Cite
|
Sign up to set email alerts
|

In situ lubricant degradation in Antarctic marine sediments. 1. Short‐term changes

Abstract: A large-scale, in situ experiment was set up near the Bailey Peninsula area (Casey Station, East Antarctica) to monitor the natural attenuation of synthetic lubricants in marine sediments over five years. Here, we report the short-term changes after 5 and 56 weeks. The lubricants tested were an unused and used Mobil lubricant (0W/40; Exxon Mobil, Irving, TX, USA) and a biodegradable alternative (0W/20; Fuchs Lubricants, Harvey, IL, USA). Clean sediment was collected, contaminated with the lubricants, and deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…These findings are consistent with Powell et al (2007), who observed that the longevity of hydrocarbons in Antarctic marine sediments can be variable, even within a relatively small geographical area. Associated with this five-year investigation at O'Brien Bay, Thompson et al (2006) investigated the biodegradation of used, unused and biodegradable lubricants in marine sediments. After five weeks, a 37% decrease in the concentration of biodegradable lubricants was observed while used and unused lubricant concentrations decreased by 20%.…”
Section: Bioremediationmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with Powell et al (2007), who observed that the longevity of hydrocarbons in Antarctic marine sediments can be variable, even within a relatively small geographical area. Associated with this five-year investigation at O'Brien Bay, Thompson et al (2006) investigated the biodegradation of used, unused and biodegradable lubricants in marine sediments. After five weeks, a 37% decrease in the concentration of biodegradable lubricants was observed while used and unused lubricant concentrations decreased by 20%.…”
Section: Bioremediationmentioning
confidence: 99%
“…After five weeks, a 37% decrease in the concentration of biodegradable lubricants was observed while used and unused lubricant concentrations decreased by 20%. Failure of the biodegradable lubricant to break down to recognized biodegradable thresholds and the resistance of lubricant additives, alkylated naphthalenes and diphenylamines, to degradation presented concerns because of their environmental toxicity (Thompson et al 2006). Antarctic marine bacteria isolated from Terra Nova Bay have also shown to exhibit gradual mineralization of diesel at 48C, with 57% degraded compared to 86% degraded at 208C following 60 days incubation (Michaud et al 2004).…”
Section: Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Field methods. The site, set-up and sampling of this field experiment have been described in detail previously (Powell et al 2005b, Thompson et al 2006. Briefly, clean, uncontaminated sediment was collected from O'Brien Bay (66°18' S, 110°32' E), near Casey station, sieved at 500 µm to remove infauna and then spiked with one of 4 oils or left as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Total oil concentrations decreased between 17 and 29% compared with the initial levels and resolved n-alkanes were depleted in weathered oil fractions. Combining the assay responses with chemical data indicated that the observed declining toxicity probably was not caused by analyzed PAH, but by other specific oil constituents Thompson et al (2006). monitored natural attenuation of synthetic lubricants (Mobil lubricant 0W/40, and Fuchs lubricant 0W/20 (a biodegradable alternative)) in an Antarctica oiled sediment experiment, but they did not monitor toxicity.…”
mentioning
confidence: 99%